Historiographical study of literature on Oman-Malay world relations: a brief analysis - Mansor Majdin, Mohamad Firdaus; Fathil, Fauziah (2021)
The long-established connections between the Middle East and Malay World have often drawn attention and interest among scholars to indulge in various studies particularly regarding socio-cultural and economic relations between the two regions. In conducting these studies, sufficient and reliable materials or literature are indeed indispensable, without which comprehensive observations are not possible. This paper attempts to explore and examine the nature and type of information contained in some identified sources, both Malay and Arabic literatures, pertaining to the relations between a Middle Eastern or Gulf state, namely Oman, and the Malay World. Not only do they describe commercial relations between Oman and the Malay World, but also contain geographical and social-cultural commentaries which call for further discussion and scrutiny. Using a method of content analysis in examining both the Malay and Arabic literatures, this paper demonstrates the multiple aspects of the sources with different thematic descriptions and ways of narratives hence, indicating none other than the wide range and diversity of the literature under study.